Structural and optical properties of phosphate-zinc-nickel oxide glasses for narrow band pass absorption filters. Issue 15 (2nd September 2018) - Emara, Ashraf M.; Yousef, El Sayed
Abstract: Novel two phosphate glass systems with compositions 50P2 O5 –30ZnO–20NiO and 50P2 O5 –30ZnO–20[NiCl2–6 H2 O] were prepared using a conventional melt-quench technique. The absorbance and transmittance were measured using a spectrophotometer in the spectral range between 190 and 1100 nm. The data demonstrates that the system acts as a narrow bandpass optical absorption filter, with a transmission band in the UV region of 311–376 nm, which is centred at 350 nm and has a full width half maximum (FWHM) of almost 34 nm, whereas, the red region is the UV region of 617–684 nm, and centred at 650 nm and has a full width half maximum (FWHM) of nearly 32 nm. However, the refractive index ( n ), optical band gap ( E opt ), non-linear refractive index n 2, third order non-linear susceptibility χ (3) and non-linear absorption coefficient β were also calculated. It was apparent that the non-linear refractive index, third order non-linear susceptibility and non-linear absorption coefficient increases by decreasing the optical energy gap. Finally, we investigated the structure of the prepared glasses by using Raman and FTIR spectra. We found that the local network structure based mainly on Q 1 and Q 2 tetrahedron units connected by P–O–P linkages.